2017
DOI: 10.1007/s00455-017-9866-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Position on Pharyngeal Swallowing Pressures Using High-Resolution Manometry

Abstract: The effect of body position and gravitational pull on the complex pressure-driven process of pharyngeal swallowing remains unknown. Using high-resolution manometry (HRM), this study aims to identify positional adaptations of pharyngeal physiology by evaluating swallowing pressure patterns in a series of inverted body positions. Ten healthy adults each underwent swallowing tasks with pharyngeal HRM at six body positions using an inversion table (0°[upright], 45°, 90°[supine], 110°, 135°, and 180°[fully inverted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 43 publications
1
14
0
7
Order By: Relevance
“…[6][7][8] Existing literature describes the UES pressure wave during swallowing as an elevated resting (basal) pressure, a period of low pressure (relaxation), a post-deglutitive increase in pressure, and a return to resting pressure. 14 However, although these elements of UES opening have been documented in the literature, the swallowing mechanics underlying the generation of the HRPM UES pressure wave, particularly why there is an elevation of pressure prior to relaxation, have not been fully investigated. Omari et al also revealed how changes in mechanical states can be deduced by recording changes in pressure and diameter within the HRPM UES region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Existing literature describes the UES pressure wave during swallowing as an elevated resting (basal) pressure, a period of low pressure (relaxation), a post-deglutitive increase in pressure, and a return to resting pressure. 14 However, although these elements of UES opening have been documented in the literature, the swallowing mechanics underlying the generation of the HRPM UES pressure wave, particularly why there is an elevation of pressure prior to relaxation, have not been fully investigated. Omari et al also revealed how changes in mechanical states can be deduced by recording changes in pressure and diameter within the HRPM UES region.…”
Section: Introductionmentioning
confidence: 99%
“…13 Other variables that affect the timing and magnitude of the pressure wave include bolus volume 5,12 and body position. 14 However, although these elements of UES opening have been documented in the literature, the swallowing mechanics underlying the generation of the HRPM UES pressure wave, particularly why there is an elevation of pressure prior to relaxation, have not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…UES residual pressure , measured at the time point of maximum tongue base pressure, was extracted as a measure of downstream resistance during pharyngeal contraction 26 . Mean preswallow baseline pressure , captures UES resting pressure over a one‐second interval, 2 seconds before pre‐opening maximum pressure 23 . The following previously described UES regional parameters were also evaluated: maximum pre‐opening pressure , maximum postclosure pressure , nadir pressure (averaged over 0.25 seconds) , and nadir pressure duration 16,23,25 …”
Section: Methodsmentioning
confidence: 99%
“…Wong et al (Wong et al, 2017) showed that the trajectory of the hyoid bone and the extent of larynx elevation in different subjects are adapted to maximize airway protection. The pressures generated in the velopharynx were found to be dependent on the body position (Rosen et al, 2017). From an engineering perspective, four main alternative swallowing control scenarios can be envisaged: -imposed displacements (with no control) -imposed forces (with no control) -355 feed-forward control adapting the applied forces or displacements to the bolus characteristics perceived before the swallow -feedback control during swallowing, adapting forces or displacements…”
Section: Swallowing Motor Control 340mentioning
confidence: 99%